2003
DOI: 10.1002/cncr.11198
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin‐1 expression is a predictor of recurrence‐free survival in pT2N0 prostate carcinoma diagnosed in Japanese patients

Abstract: Asymmetrische Bewegung: Werte für dipolare Kopplungstensoren aus Festkörper‐NMR‐Messungen geben Einblick in die Dynamik von Proteinen. Auch die bislang unbeachtete Asymmetrie des dipolaren Kopplungstensors liefert wertvolle Informationen über die Asymmetrie einer Bewegung, mit deren Hilfe solche Tensoren erstmals direkt und ortsaufgelöst gemessen werden konnten. Wichtige Bewegungen wie Rotamersprünge lassen sich nun im Festkörper direkt detektieren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 47 publications
(49 reference statements)
6
46
1
1
Order By: Relevance
“…This is in agreement with previous studies that have indicated that Caveolin-1 is responsible for tumour aggressiveness in prostate cancer [9]. Increases in Caveolin-1 expression have already been reported in clinically aggressive disease with higher preoperative PSA levels and Gleason scores [12][13][14]16], advanced tumour stage [17], positive surgical margins [13,16,18] and lymph node metastases [13,17]. Evidence suggests that Caveolin-1 contributes to aggressive features through different mechanisms including anti-apoptotic properties and increased angiogenesis [11].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in agreement with previous studies that have indicated that Caveolin-1 is responsible for tumour aggressiveness in prostate cancer [9]. Increases in Caveolin-1 expression have already been reported in clinically aggressive disease with higher preoperative PSA levels and Gleason scores [12][13][14]16], advanced tumour stage [17], positive surgical margins [13,16,18] and lymph node metastases [13,17]. Evidence suggests that Caveolin-1 contributes to aggressive features through different mechanisms including anti-apoptotic properties and increased angiogenesis [11].…”
Section: Discussionsupporting
confidence: 91%
“…This association remained significant when adjusted for standard clinicopathological characteristics. Several studies have investigated tissue expression of Caveolin-1 after RP and similarly reported Caveolin-1 as a predictor of poor clinical outcome [12][13][14]18]. Karam et al [12] reported an independent association with aggressive PSA recurrence defined by a positive metastatic evaluation, PSA doubling time of <10 months, and/or failure to respond to local salvage radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up-regulation of CAV1 is associated with more aggressive behavior, increased recurrence rate and poorer prognosis (32)(33)(34)(35)(36). Increased CAV1 expression has recently been reported in multidrug-resistant neoplastic cells, suggesting its specific role in the acquisition and maintenance of this phenotype (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…(9,10) Prostate cancer patients with higher levels of Cav-1 showed a shortened interval to disease recurrence following therapy for localized disease and are usually associated with a higher Gleason score pathologically. (11)(12)(13)(14) Cav-1-mediated oncogenic activities in prostate cancer are linked to two pathways: first, overexpressed Cav-1 interacts directly with cellular signaling factors to stimulate proliferation and to activate anti-apoptotic mechanisms. (15)(16)(17)(18)(19) In cultured prostate cancer cells, up-regulated Cav-1 binds and inhibits protein phosphatases PP1 and PP2A and results in constantly active PI3K/Akt pathway.…”
Section: Introductionmentioning
confidence: 99%